Magnificence : a novel - Millet, Lydia, 1968- (New York : W.W. Norton & Co., 2013)
Still mourning the death of her husband, Susan Findley is given a chance at reclamation when she inherits her grand- uncle's enchanting Pasadena, CA, mansion and immediately sets about to restore its taxidermy collection to pristine perfection. Alas, a few less than pristine relations drop in to stay.
Keywords: Widows -- Fiction; Taxidermy -- Fiction; Life change events -- Fiction; Inheritance and succession -- California -- Fiction; Shared housing -- Fiction; Black humor (Literature).